Endocarditis and systemic embolization from Whipple's disease. (2021) - He, Yu Ting; Peterson, Katherine; Crothers, Jessica; Dejace, Jean; Hale, Andrew J.
Abstract: Whipple's disease (WD), caused by infection with the organism Tropheryma whipplei, is a rare disease that classically presents with diarrhea, weight loss, and polyarthralgia. Less commonly, Whipple's Disease can presentation with endocarditis or neurologic infections. The authors report a patient with Whipple's Disease endocarditis whose initial presentation was acute lower extremity arterial occlusion, and review current literature regarding the epidemiology, diagnosis, treatment, and prognosis of Whipple's Disease endocarditis.